Analisis Aerodinamika Rancangan Body City Car dengan Penambahan Spoiler Belakang Menggunakan Ansys Fluent - Ananda, Yoga Rizki; Putra, Randi Purnama; Fernanda, Yolli; Qalbina, Fitrah (Lembaga Yasin AlSys, 2025)
An increase in the number of fossil fuel vehicles leads to increased energy consumption and exhaust emissions, which have a negative impact on the environment. One way to improve fuel efficiency is to optimize vehicle aerodynamic design, especially through the addition of a rear spoiler. This study aims to analyze the effect of city car body design with the addition of a rear spoiler on vehicle aerodynamic characteristics, such as drag coefficient, lift coefficient, and the ratio between the two. The research method used is numerical simulation with Computational Fluid Dynamics (CFD) using Ansys Fluent 2024 R1 Student Version software. The simulation was performed on a 3D city car model with airflow velocity variations of 10 m/s, 20 m/s, and 30 m/s. The data obtained were analyzed using grid independency analysis techniques to ensure the accuracy of the simulation results. The results show that the addition of a rear spoiler is able to reduce the lift coefficient thereby improving vehicle stability, although there is a slight increase in the drag coefficient as the airflow velocity increases. The negative ratio between the lift coefficient and drag coefficient indicates that the lift is downforce, which contributes to vehicle stability at high speeds. A suggestion from this research is the optimization of the spoiler shape to further reduce the drag coefficient without compromising vehicle stability. Further research can be conducted by testing variations in spoiler design and lighter materials for better aerodynamic efficiency.